2021
DOI: 10.1177/13684302211010923
|View full text |Cite
|
Sign up to set email alerts
|

Social and ecological dominance orientations: Two sides of the same coin? Social and ecological dominance orientations predict decreased support for climate change mitigation policies

Abstract: In this article, we examine the roles of social dominance orientation (SDO) and ecological dominance orientation (EDO) as predictors of climate change risk and threat perceptions and associated pro-environmental policy support. EDO is a novel measure that we devised based on social dominance theory to assess general preferences for an anthropocentric, hierarchical arrangement between humans, non-human animals, and the natural environment. Across two pre-registered studies ( N = 715; USA and Germany) our result… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 64 publications
1
13
1
Order By: Relevance
“…We concur with these basic assumptions that SDO generalizes onto the interspecies and human-environment domains via support for hierarchy-legitimizing myths and acknowledge and build upon the insights provided hitherto. However, in contrast to these explanations, in a previous study, we have argued that ecological dominance might represent a psychologically meaningful and distinct entity in and for itself (Uenal, Sidanius, & van der Linden, 2021). More to the point, we have argued that ecological dominance might qualify as an independent upstream predictor of hierarchy-legitimizing myths with downstream consequences.…”
Section: The Roots Of Ecological Dominance Orientation: Assessing Ind...contrasting
confidence: 60%
See 4 more Smart Citations
“…We concur with these basic assumptions that SDO generalizes onto the interspecies and human-environment domains via support for hierarchy-legitimizing myths and acknowledge and build upon the insights provided hitherto. However, in contrast to these explanations, in a previous study, we have argued that ecological dominance might represent a psychologically meaningful and distinct entity in and for itself (Uenal, Sidanius, & van der Linden, 2021). More to the point, we have argued that ecological dominance might qualify as an independent upstream predictor of hierarchy-legitimizing myths with downstream consequences.…”
Section: The Roots Of Ecological Dominance Orientation: Assessing Ind...contrasting
confidence: 60%
“…More specifically, across two studies, we have shown that SDO and EDO are (a) moderately associated with each other (raverage = .45), (b) significantly higher among male participants (vs. females), and (c) uniquely and negatively associated with climate change risk and threat perceptions and support for proenvironmental behavior. Notably, EDO was negatively associated with pro-environmental behavior (e.g., signing ostensibly real online petitions), while SDO showed no such relationship (Uenal, Sidanius, & van der Linden, 2021).…”
Section: Preliminary Researchmentioning
confidence: 94%
See 3 more Smart Citations